2020
DOI: 10.1017/rdc.2020.8
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Terrestrial Macrofossils

Abstract: Acid-alkali-acid (AAA) pretreatment is widely used to clean terrestrial plant macrofossil samples for radiocarbon (14C) dating. There is wide variation amongst laboratories in the AAA method details and less rigorous AAA pretreatment is often used on fragile or small samples. Yet there is little evidence as to the efficacy of the different methods and whether the use of less rigorous methods is justified. We investigated four variations of AAA pretreatment: acid only (no alkali wash); room temperature AAA; “st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
(47 reference statements)
0
9
0
1
Order By: Relevance
“…Terrestrial leaf macrofossils were extracted by picking in situ material from the split core surface. Macrofossils were cleaned and pretreated using an acid-alkali-acid procedure to remove carbonates as well as fulvic and humic compounds (Norris et al, 2020). The pretreated macrofossils were converted to CO 2 by combustion, graphitized, and measured by accelerator mass spectrometry as described by Baisden et al (2013).…”
Section: Core Chronologymentioning
confidence: 99%
“…Terrestrial leaf macrofossils were extracted by picking in situ material from the split core surface. Macrofossils were cleaned and pretreated using an acid-alkali-acid procedure to remove carbonates as well as fulvic and humic compounds (Norris et al, 2020). The pretreated macrofossils were converted to CO 2 by combustion, graphitized, and measured by accelerator mass spectrometry as described by Baisden et al (2013).…”
Section: Core Chronologymentioning
confidence: 99%
“…However, which method is the most suitable remains a matter of debate, though some methodological trials that have compared the main pre-treatment techniques (Acid Oxidation [ABOX] and Acid-Alkaline-Acid or Acid-Base-Acid [AAA or ABA]) have concluded that the former produces superior results to the latter (Haesaerts et al, 2013;Maroto et al, 2012). This finding has been corroborated by a recent study (Norris et al, 2020) which analyses the different varieties of AAA pre-treatment in detail, and concluded that they should involve more than the simple application of acid to the sample.…”
Section: Sample Pre-treatment / Ultrafiltration: a New Problem?mentioning
confidence: 91%
“…Targets for 14 C dating were limited to terrestrial leaf macrofossils collected by picking from the split core surface or by sieving sequential 1-cm core slices. Macrofossils were cleaned of residual sediment under a dissecting microscope and chemically pretreated to remove carbonates, fulvic and humic compounds using an acid-alkaline-acid pretreatment (Norris et al, 2020). Using the protocol described by Baisden et al (2013), the cleaned macrofossils were converted to CO 2 by combustion, graphitized, and measured by accelerator mass spectrometry at the Rafter Laboratory.…”
Section: Sediment Core Chronologymentioning
confidence: 99%